The role of visual cortex acetylcholine in learning to discriminate temporally modulated visual stimuli - Minces, Victor H.; Alexander, Andrew; Datlow, Mitchell; Alfonso, Stephanie; Chiba, Andrea A. (Frontiers in Behavioral Neuroscience, 2013)
Cholinergic neurons in the basal forebrain innervate discrete regions of the cortical mantle, bestowing the cholinergic system with the potential to dynamically modulate sub-regions of the cortex according to behavioral demands. Cortical cholinergic activity has been shown to facilitate learning and modulate attention. Experiments addressing these issues have primarily focused on widespread cholinergic depletions, extending to areas involved in general cognitive processes and sleep cycle regulation, making a definitive interpretation of the behavioral role of cholinergic projections difficult. Furthermore, a review of the electrophysiological literature suggests that cholinergic modulation is particularly important in representing the fine temporal details of stimuli, an issue rarely addressed in behavioral experimentation. The goal of this work is to understand the role cholinergic projections, specific to the sensory cortex, in learning to discriminate fine differences in the temporal structure of stimuli. A novel visual Go/No-Go task was developed to assess the ability of rats to learn and discriminate fine differences in the temporal structure of visual stimuli (lights flashing at various frequencies). The cholinergic contribution to this task was examined by selectively eliminating acetylcholine projections to visual cortex (using 192 IgG-saporin), either before or after discrimination training. We find that in the face of compromised cholinergic input to the visual cortex, the rats’ ability to learn to perform fine discriminations is impaired, whereas their ability to perform discriminations remains unaffected. These results suggest that acetylcholine serves the role of facilitating plastic changes in the sensory cortices that are needed for an animal to refine their sensitivity to the temporal characteristics of relevant stimuli.